Evaluation of the frequency of intra-oral radiographic errors in dental radiology department in Mashhad - Azam Ahmadian Yazdi; Samareh Mortazavi; Hosein Saeedi Moghaddam (Tehran University of Medical Sciences, 2019)
Background and Aims: Dental diagnosis may be affected by the occurrence of the errors in the intra-oral radiographic images and the patients' treatment plan can be problematic in these cases. The repetition of these radiographs increases the risks of radiation exposure for the patients in turn. The present study assessed the incidences of common periapical radiographic errors taken by dental students in oral and maxillofacial radiology department of Mashhad dental school in 2017. Materials and Methods: In this cross-sectional descriptive study, 1470 periapical radiographs prepared by student during a semester of 2017 were collected and evaluated. Radiographic observations were done and the incidence of conventional radiographic errors were determined. Finally, the frequency and percentage of radiographic errors were determined based on the type of radiography sex, the age of the patient, and the history of radiography. Then, results were analyzed using the Chi-Square test and SPSS19 (P=0.05). Results: Film placement (27.2%), cone-cut (27.2%), elongation (13.2%) and horizontal angle (10.9%) were reported as the most common radiographic errors. The repetition rate of the radiographs was 2.9%; among them, the highest errors were Cone-cut errors in the upper jaw Conclusion: Based on the results of this study, the most radiographic errors included film position and Cone-cut errors and these two errors were the most frequent cause of repetitive radiographies that required the provision of specific training for the prevention of these errors.